Reflection color tuning of a metal-insulator-metal cavity structure using arc plasma deposition of gold nanoparticles - Kim, Yun Hee; Rahman, M. A.; Hwang, Jong Seung; Ko, Hyungduk; Huh, Joo-Youl; Byun, Ji Young (ELSEVIER, 2021)
Structural colors have diverse applications in optical filters, surface decoration, photovoltaics, and digital displays. In this study, an arc plasma deposition (APD) method was employed for fabrication of the top Au layer in the asymmetric Fabry-Perot cavity structure of Au/Si3N4/Al. With an increasing number of APD pulses (nP), the morphology of the Au layer gradually changed from a dispersion of nanoparticles (NPs) to a nanoporous film and then to a dense film, which in turn led to a change in the refractive index of the Au layer. The structural colors of the Au/Si3N4/Al structure were mainly governed by the interference effect. The optical constants of the NPdispersed and nanoporous Au layers could be reasonably estimated based on Bruggeman's effective medium approximation. When the Au layers deposited with different nP were combined with dielectric Si3N4 layers of various thicknesses (hd), the full range of color hue with a wide range of color chroma could be realized using the Au/Si3N4/Al trilayer structure. The color hue was predominantly governed by hd, and the color chroma gradually increased with nP for a given value of hd.
Keywords: PHOTONIC CRYSTAL FILMS; LARGE-AREA; ABSORBERS; SURFACE; FILTERS; AU